Network Pharmacology Suggests Mechanisms for Therapeutic Effects of Caulis Sinomenii on Avian Gout - Guanyang Li; Junfei Xu; Huanhuan Li; Wenxin Yan; Fengting Chen; Anwen Yuan; Juzuo Zhang (The Journal of Poultry Science)
Avian gout (AG) is detrimental to the survival and production performance of poultry and effective drugs are lacking. Caulis sinomenii has shown clinical efficacy against arthritis and may have potential value in AG prevention and treatment. In the present study, the components and targets of C. sinomenii and AG-related targets were identified using relevant databases. The common targets, target interactions, and signaling pathways involved in the prevention and treatment of AG by C. sinomenii were determined using software to explore the potential mechanisms of action. Sixteen components of C. sinomenii, eight of which were active ingredients with 351 targets and 2993 AG-related targets, were identified using several databases. A total of 156 common targets were associated with 202 biological processes and 34 pathways. Toll-like receptor 4 (TLR4) and prostaglandin endoperoxide synthase 2 were core targets. These targets may exert therapeutic effects on AG through four pathways: the nucleotide-binding oligomerization domain (NOD)-like receptor, mammalian target of rapamycin, TLR, and mitogen-activated protein kinase signaling pathways. In summary, C. sinomenii has potential therapeutic efficacy against AG through multicomponent, multi-target, and multi-pathway mechanisms.